Cross-cultural variations in ESL/EFL female learners' product, process, and perceptions in collaborative tasks - Yazdi Amirkhiz, Seyed Yasin (2012)
Collaborative writing has been approached and investigated from various perspectives in the relevant literature. The purpose of this study was three-fold: to investigate the influence of collaborative writing on the quality of individual writing (Product), the verbal interactions between the peers during collaborative writing sessions Process), and Perceptions of participants towards collaborative writing (learning). The study involved eight participants who were divided into two EFL (i.e., Iranian) and two ESL (i.e., Malaysian) homogeneous dyads. To investigate the Product, the dyads performed collaborative writing for 15 sessions; after any three consecutive collaborative writing sessions, each participant was asked to carry out a writing task individually. The tasks used in both collaborative and individual writing were isomorphic graphic prompts (IELTS Academic Module task 1). The writing quality of five individually-produced texts was determined in terms of task achievement (TA), cohesion/coherence (C/C), grammatical range/accuracy (GR/A), and lexical resources (LR). The findings showed the most positively-affected areas among all the participants were TA front, followed by C/C front. GR/A did not display any improvement among EFL/ESL participants, and LR showed minor improvement only among three of ESL participants. Also, regression was a frequent incident among the participants. The findings are discussed in the light of the socio-cultural perspective of learning, emergentist perspective (one that is informed by chaos complexity theory), cultural background of the participants, the typology of tasks used, the role of the participants language proficiency, and participants collaborative dynamics during collaborative writing sessions. To examine the Process, the pair talk was audio-recorded and transcribed for each dyad. The transcribed data were segmented at three levels (type of talk, type of activity and episodes). The findings indicated certain similarities and differences among the EFL and ESL dyads. The most remarkable discrepancy was related to the Language Related Episodes (LREs). It was revealed that EFL/ESL dyads had different orientations towards metatalk; EFL dyads tended to focus considerably more on meta-linguistic features of language than ESL dyads. The findings are discussed with a reference to the different status of the English language in the two contexts of Iran and Malaysia (i.e., EFL vs. ESL) as well as the effect of previous educational experiences of the learners. To investigate the Perceptions, data came from a number of sources: interviews, observations, stimulated recalls, participants language learning histories and content analysis of the pair talk for the pronouns (i.e., first-person and second person pronouns). Existence of numerous sources of data and methods made triangulation of the findings possible. Interviews revealed that despite some similarities in the mindset of EFL/ESL participants towards collaborative learning,here were notable divergent attitudes towards the practice as well. Observations of the collaborative sessions and stimulated recall showed that the collaborative behavior of Malaysian participants was following a seamless pattern of acquiescence, lack of criticism and non-confrontation, whereas there were numerous instances of confrontation, inflexibility and mutual criticisms in the interactional behaviors of Iranian participants. The content analysis of the pair talk for pronouns indicated that EFL participants tended to use I and YOU considerably more than their Malaysian counterparts, whereas Malaysian participants were found to have a stronger tendency to use WE more. Comparing language learning histories of EFL/ESL participants revealed certain discrepancies. Juxtaposing these findings led the researcher to conclude that the collectivist orientation was tangibly stronger among Malaysian participants than among their Iranian counterparts. The findings are discussed with regard to the macro-cultural dichotomy of world cultures (collectivist/ individualist). The findings of this study could have a number of implications (theoretical/pedagogical). The study adds to the previous attempts to extend the socio-cultural perspective of language learning from the traditionally predominant spoken discourse to written discourse, and also extends the boundaries of the benefits of collaborative writing. The benefits go beyond lexico-grammatical level as addressed by previous studies, and encompass task achievement and cohesion/coherehnce fronts of writing proficiency as well. Another significant implication of the study is that a universalistic perception that learners of similar proficiency dealing with the identical tasks generate more or less similar patterns of LREs was challenged. More importantly, the relatively contrasting perceptions of Malaysian and Iranian students towards collaborative learning could be seen as a caution against the invariable utilization of this modality of learning in all the contexts. This in turn highlights the fact that one size might not fit all all the time, and learning and teaching should be seen as context-bound and situation-based.